Investigating the Perceived Strengths and Limitations of Free-Viewpoint Video - MacQuarrie, Andrew; Steed, Anthony (Frontiers in Virtual Reality, 2020)
Free-viewpoint video (FVV) is a type of immersive content in which a character performance is filmed using an array of cameras and processed into a video-textured, animated 3D mesh. Although FVV content has a unique set of properties that differentiates it from other immersive media types, relatively little work explores the user experience of such content. As a preliminary investigation, we adopted an open-ended, qualitative approach to investigate these issues. Semi-structured interviews were conducted with six immersive content experts, exploring the perceived strengths and limitations of FVV as a content type. These interviews were analyzed using inductive thematic analysis. We identified five themes during our analysis: they don't look real, but that's okay; they can really move; they don't connect with me; encounter, legacy, and truth; no technology is an island. Our analysis reveals a wide range of future research directions and provides insight into which areas may produce the most benefit in relation to the user experience. We discuss, for example, the potential impact of difficulties in supporting user engagement, aspects related to visual quality such as the importance of responding realistically to environment lighting, and tensions between visual and behavioral quality. The analysis also highlights the complex interplay of factors related to the content itself, such as performance style and the use of creative production techniques to reduce the impact of potential limitations.